Postacute Care Readmission and Resource Utilization in Patients From Socioeconomically Distressed Communities After Total Joint Arthroplasty. Issue 2 (21st February 2023) - Magnuson, Justin A.; Griffin, Sean A.; Venkat, Nitya; Gold, Peter A.; Courtney, P. Maxwell; Krueger, Chad A.
Abstract: Background: Racial and socioeconomic disparities have been associated with complications and poorer patient-reported outcomes after THA and TKA, but little is known regarding the variation of postacute care resource utilization based on socioeconomic difference in the communities in which patients reside. Hip and knee arthroplasty are among the most common elective orthopaedic procedures. Therefore, understanding social factors provides insight into patients at risk for readmission and the way in which these patients use other postoperative resources. This knowledge can help surgeons better understand which patients are at risk for complications or preventable readmissions and how to anticipate when additional surveillance or intervention might reduce this risk. Questions/purposes: (1) Do patients from communities with a higher distress level experience higher rates of readmission after THA and TKA? (2) Do patients from distressed communities have increased postoperative resource utilization? Methods: Demographics, ZIP code of residence, and Charlson comorbidity index (CCI) were recorded for each patient undergoing TKA or THA between 2016 and 2019 at two high-volume hospitals. Patients were classified according to the Distressed Communities Index (DCI) score of their ZIP code of residence. The DCI combines seven metrics of socioeconomic well-being (high school graduation, poverty rate, unemployment, housing vacancy, household income, change in employment, and change in establishment) to create a single score. ZIP codes are then classified by scores into five categories based on national quintiles (prosperous, comfortable, mid-tier, at-risk, and distressed). The DCI was chosen because it provides a single composite measure of multiple important socioeconomic factors. Multivariate analysis with logistic, negative binomial regression, or Poisson was used to investigate the association of DCI category with postoperative resource utilization while controlling forage, gender, BMI, and comorbidities. The primary outcome was 90-day readmissions. Secondary outcomes included postoperative medication prescriptions from the orthopaedic team, patient telephone calls to the surgeon's office, physical therapy sessions attended, follow-up office visits, and emergency department visits. A total of 5077 patients who underwent TKA (mean age 66 ± 9 years, 59% [2983 of 5077] are women, and 69% [3519 of 5077] are White), and 5299 who underwent THA (mean age 63 ± 11 years, 50% [2654 of 5299] are women, and 74% [3903 of 5299] are White) were included. Results: When adjusting for age, gender, race and CCI, readmission risk was higher in distressed communities compared with prosperous communities for patients undergoing TKA (odds ratio 1.6 [95% confidence interval 1.1 to 2.3]; p = 0.02) but not for THA. For secondary outcomes after TKA, at-risk communities had more postoperative prescriptions compared with prosperous communities, but no other differences were found. After THA, no major differences were found in the likelihood to utilize postoperative resources based on DCI category. Race was not associated with readmissions or resource utilization. Conclusion: We found that socioeconomic distress was associated with readmission after TKA, but, after controlling for relevant confounding variables, race had no association. Patients from these communities do not demonstrate an increased or decreased use of other resources after post-TKA discharge. Increased awareness of these disparities may allow for closer monitoring and improved patient education and communication, with the goal of reducing the frequency of complications and preventable readmissions. Level of Evidence: Level III, therapeutic study.